Pendidikan Islam Multiliteral: Kajian Pemikiran Imam Nawawi dalam Adabul Alim Wal Mutaalim - Suandi, Ari (Ta'allum: Jurnal Pendidikan Islam, 2019)
The philosophy of Islamic education thought today leads to technical education methods. Not many realize that the practice of Islamic education is confined by monolithic disciplinary arrogance. Monolithic Islamic education, which has been a solution to answer various types of conflicts, often triggers new conflicts. So far Islamic education has not found a paradigmatic grounding. This article analizes the thaughts of Nawawi’s in Adabul Alim Wal Muta’alim. Ideally, Islamic education as a solution can come through relationships variety, which can be elaborated by multiliteral diversity. Nawawi in the book of Adabul Alim Wal Mutaalim has presented the concept of multiliteral Islamic education with four relations; that is, theocentric relations, linguistic relations, ethical relations, and juridical relations. At this point, the study of the Nawawi priest’s thoughts through the Adabul Alim Wal Muta’allim book as a strategic step to portray the concept of multiliteral Islamic education found its paradigmatic footing.